1999
DOI: 10.1093/bja/82.1.8
|View full text |Cite
|
Sign up to set email alerts
|

‘Alveolar recruitment strategy’ improves arterial oxygenation during general anaesthesia

Abstract: Abnormalities in gas exchange during general anaesthesia are caused partly by atelectasis. Inspiratory pressures of approximately 40 cm H2O are required to fully re-expand healthy but collapsed alveoli. However, without PEEP these re-expanded alveoli tend to collapse again. We hypothesized that an initial increase in pressure would open collapsed alveoli; if this inspiratory recruitment is combined with sufficient end-expiratory pressure, alveoli will remain open during general anaesthesia. We tested the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1
17

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(94 citation statements)
references
References 0 publications
3
73
1
17
Order By: Relevance
“…Tusman e col. registraram valores semelhantes de pressão nas vias aéreas na melhora da oxigenação após anestesia para cirurgia geral. Há poucos relatos da utilização da MRA em procedimentos cirúrgicos cardíacos 11,12 . Dyhr e col. 6 definiram a MRA como sendo a aplicação de quatro insuflações sustentadas com pressão nas vias aéreas de 45 cmH 2 O por 10 segundos cada, na modalidade CPAP do ventilador.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Tusman e col. registraram valores semelhantes de pressão nas vias aéreas na melhora da oxigenação após anestesia para cirurgia geral. Há poucos relatos da utilização da MRA em procedimentos cirúrgicos cardíacos 11,12 . Dyhr e col. 6 definiram a MRA como sendo a aplicação de quatro insuflações sustentadas com pressão nas vias aéreas de 45 cmH 2 O por 10 segundos cada, na modalidade CPAP do ventilador.…”
Section: Discussionunclassified
“…Cuidados foram tomados quanto à presença de quaisquer vazamentos que pudessem prejudicar a leitura do volume exalado e da manutenção da pressão nas vias aéreas. A MRA neste trabalho foi semelhante, porém com pequenas modificações ao método preconizado na literatura 12 não havendo diferença estatística significativa (p > 0,05) entre ambos os grupos. Todos os pacientes apresentaram evolução clínica satisfatória, tendo sido extubados e recebendo alta da UTI no período de 48 horas.…”
Section: Métodounclassified
“…Bendixen et al [4] and later Rothen et al [7] showed that this pressure is approximately 40 cm H 2 O. Lachmann et al [8] recommended opening collapsed lungs by applying sufficient levels of peak inspiratory pressure and maintaining alveoli open by using sufficient levels of positive end-expiratory pressure (PEEP). This recruitment maneuver has been shown to improve arterial oxygenation and lung compliance [9]. Tusman et al [9] showed that the frequency of atelectasis was much less following the alveolar recruitment strategy peak airway pressure of 40 cm H 2 O and a PEEP of 15 cm H 2 O for 10 breaths.…”
Section: Anesthetic Concernsmentioning
confidence: 99%
“…This recruitment maneuver has been shown to improve arterial oxygenation and lung compliance [9]. Tusman et al [9] showed that the frequency of atelectasis was much less following the alveolar recruitment strategy peak airway pressure of 40 cm H 2 O and a PEEP of 15 cm H 2 O for 10 breaths. PEEP was then reduced to and kept at 5 cm H 2 O.…”
Section: Anesthetic Concernsmentioning
confidence: 99%
“…24 Measures to increase FRC such as application of positive end-expiratory pressure (PEEP) are sometimes successful, and less commonly, intermittent sigh breaths. 25 Harvey and Ellis studied the e ect of continuous positive airways pressure (CPAP) in acute tetraplegia and demonstrated that the FRC could be increased by the application of PEEP but only for so long as the PEEP was being applied. 26 Technical di culties precluded measurements of CV in these tetraplegic patients.…”
Section: Acid-base and Electrolytesmentioning
confidence: 99%